MICROSTRUCTURAL CHARACTERIZATION OF DUPLEX STEEL FOR WELDED INSTALLATIONS USING DIGITAL IMAGE PROCESSING - Cruz Crespo, Amado; Miguel Oria, Jorge Victor; Valencia Morales, Eduardo; Pozo Morejón, Juan A.; De Souza Bott, Ivani (Centro Azúcar Journal, 2023)
Introduction: The microstructural characterization of duplex steels makes it possible to define their behavior during fabrication by welding installation and during service. Objective: To characterize, from the microstructural point of view, a duplex steel for its use in installations manufactured by welding, using digital image processing. Materials and Methods: With the use of digital image processing, the fraction of austenite and ferrite in duplex steel is determined. The Heat Affected Zone of GMAW welding is also characterized, taking into account two values of energy input. The fraction of ferrite and of the different morphologies of austenite is quantified; as well as the grain size and the width of the HAZ. Results and Discussion: Digital image processing makes it possible to quantify the different austenite morphologies. The effect of heat input on the ferrite fraction and the different austenite morphologies and on the width and grain size in the Heat Affected Zone is established. Conclusions: The validity of digital image processing for the microstructural characterization of duplex steels subjected to welding is ratified. For the energy of 1.5 kJ most of the austenite is grain boundary, followed by Witmastatten and lastly intragranular. For the energy of 2.5 kJ, the grain boundary decreases significantly, the Witmastatten and the intragranular increase. For installations to be manufactured by welding, the use of the lowest possible input energy is recommended.